Impact of methods and solvents on bio-oil extraction from Nannochloropsis oculata: experimental and statistical analysis - Cosme, Lyon Lopes; Bacelos, Marcelo Silveira; Bento, Nicholas Alexandre Berger; Porto, Paulo Sérgio da Silva (Latin American Journal of Energy Research, 2025)
The use of microalgae for biofuel production has gained increasing interest because of their high productivity, rapid growth rate, and CO₂ fixation ability. Among the process steps, lipid extraction is considered one of the most critical and expensive, mainly depending on the solvent and method used. Although nonpolar solvents like hexane and assisted methods such as ultrasound are commonly employed, there is still debate about the most effective combination to maximize extraction yield. Therefore, this study aimed to evaluate how the solvent (hexane, dichloromethane, and a mixture of hexane + dichloromethane) and the extraction method (agitation, ultrasound, and agitation + ultrasound) influence the efficiency of bio-oil extraction from the microalga Nannochloropsis oculata. Nine experiments were conducted in duplicate, and the results were analyzed using two-way factorial ANOVA and Tukey’s HSD test (p < 0.05). The findings revealed significant differences between the tested factors and showed a notable interaction between solvent and method. The combination of hexane + ultrasound (H+U) produced the highest average extraction yield (14.95% ± 0.41), followed by dichloromethane + ultrasound (10.06% ± 0.62), and hexane + dichloromethane with agitation + ultrasound (9.87% ± 0.35). Ultrasound consistently improved efficiency, regardless of the solvent used. The lack of a synergistic effect with the H+D mixture indicates that combining solvents does not necessarily increase yield. Overall, the combination of hexane and ultrasound proved to be the most effective condition for extracting bio-oil from N. oculata, offering a promising alternative for sustainable biofuel production.